2019
DOI: 10.1016/j.fertnstert.2019.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Phytoestrogen exposure alters endometrial stromal cells and interferes with decidualization signaling

Abstract: Objective: To investigate whether phytoestrogens (genistein and daidzein) alter in vitro decidualization of human endometrial stromal cells (ESCs). Design: Isolated primary ESCs were exposed to phytoestrogens and decidualized in vitro. Setting: Academic fertility center. Patient(s): Twenty fertile oocyte donors attending the IVI Valencia clinic. Intervention(s): Treatment of ESC with phytoestrogens at 0, 10, 20, 50, and 100 mM. Main Outcome Measure(s): The ESC proliferation was analyzed by MTS assay. In vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…However, VFE treatment ameliorated uterine atrophy and tissue weight loss observed in untreated OVX rats. A previous study has shown that phytoestrogens such as genistein and daidzein can alter endometrial stromal cells and interfere with decidualization signaling [38]. We also confirmed that VFE increased the protein expression of ER-α and blood estradiol levels.…”
Section: Discussionsupporting
confidence: 85%
“…However, VFE treatment ameliorated uterine atrophy and tissue weight loss observed in untreated OVX rats. A previous study has shown that phytoestrogens such as genistein and daidzein can alter endometrial stromal cells and interfere with decidualization signaling [38]. We also confirmed that VFE increased the protein expression of ER-α and blood estradiol levels.…”
Section: Discussionsupporting
confidence: 85%
“…In rats, phytoestrogen exposure during the fetal and early neonatal stage is associated with long term alterations to the estrous cycle after the exposed individuals reach puberty, with prolonged suppression of ovarian cycling ( 117 ) and inhibition of LH secretion ( 118 ). Neonatal exposure to genistein might create a more hostile uterine environment that is less capable of supporting embryo implantation ( 103 , 119 ). In addition to these reproductive consequences, in utero exposure to estrogenic compounds also impairs immune function in rats ( 120 ), increases the incidence of cancerous lesions in the uterus ( 121 , 122 ), and impairs the development of estrogen-sensitive organs, particular secondary sex organs ( 123 , 124 ).…”
Section: The Timing Of Phytoestrogen Exposure Is Critical For Reprodu...mentioning
confidence: 99%
“…However, in primary cultures of human endometrial stromal cells, genistein (1 nmol/L to 1 mmol/L) upregulated the expression of aromatase activity and increase the aromatase activity, suggesting that genistein could modify the natural course of endometriosis thorough affecting local estrogen biosynthesis. Also in endometrial stromal primary cultures, Salsano et al observed that 10, 20, 50, and 100 µmol/L of genistein, daidzein, or genistein + daidzein inhibited cell proliferation and prolactin secretion, and induced in vitro decidualization, in a dose-dependent manner [85]. Srisomboon et al demonstrated that in the primary culture of porcine endometrial epithelial cells, genistein and daidzein enhanced β-defensins (PBD)-2 expression and PBD-2 and PBD-3 secretion [86].…”
Section: Findings From In Vitro Studiesmentioning
confidence: 99%